2009
DOI: 10.1007/s11199-009-9704-7
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Gender Identity in Lesbian and Heterosexual Two-Parent Families

Abstract: This study compared gender identity, anticipated future heterosexual romantic involvement, and psychosocial adjustment of children in lesbian and heterosexual families; it was furthermore assessed whether associations between these aspects differed between family types. Data were obtained in the Netherlands from children in 63 lesbian families and 68 heterosexual families. All children were between 8 and 12 years old. Children in lesbian families felt less parental pressure to conform to gender stereotypes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 39 publications
5
80
0
11
Order By: Relevance
“…The scale consists of separate versions for boys and girls. The Dutch translation and answering format with a 4-point likert scale (completely disagree, disagree, agree, completely agree) are based on the work of Bos and Sandfort (2010). This scale was constructed using mean sum of scores, with high scores indicating more pressure for gender conformity.…”
Section: Pressure For Gender Conformitymentioning
confidence: 99%
“…The scale consists of separate versions for boys and girls. The Dutch translation and answering format with a 4-point likert scale (completely disagree, disagree, agree, completely agree) are based on the work of Bos and Sandfort (2010). This scale was constructed using mean sum of scores, with high scores indicating more pressure for gender conformity.…”
Section: Pressure For Gender Conformitymentioning
confidence: 99%
“…Although Italian studies of same-sex parenting are scarce, empirical evidence from studies conducted primarily in North America and Northern Europe indicate that parenting effectiveness is not linked to parental sexual orientation and that children with same sex parents are typically as well-adjusted as children with heterosexual parents (in Northern Europe: Bos and Sandfort 2010;Bos et al 2007;in North America: Wainright et al 2004;Wainright, and Patterson 2006). Studies comparing children raised by lesbian or gay parents with children raised by heterosexual parents have discovered no significant differences in terms of children's social and emotional adjustment, gender role identification, or sexual orientation (in Northern Europe: Golombok et al 1983;Golombok and Tasker 1996;in North America: Farr et al 2010;Fulcher et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As before, parental and teacher reports on the CBCL indicated that children from lesbiancouple families did not differ from the two heterosexual-couple groups in their adjustment, and their scores looked similar to Dutch norms. No differences were found in gender role development (see also Bos and Sandfort 2010). Later, more extensive assessment of the children's wellbeing at age ten indicated much the same pattern of development, with the exception that teachers reported more attention problems in the lesbian couples' children than in the children of CC heterosexual couples (a DI heterosexual couple group was not included).…”
mentioning
confidence: 83%